2013
DOI: 10.1136/bmjopen-2013-003583
|View full text |Cite
|
Sign up to set email alerts
|

What happens when patients know more than their doctors? Experiences of health interactions after diabetes patient education: a qualitative patient-led study

Abstract: ObjectiveTo explore the impact of patient education on the lives of people with diabetes, including the effect on interactions with doctors and other healthcare professionals.DesignQualitative user-led study using longitudinal interviews and 146 h of participant observation. Data were analysed using a narrative approach.Participants21 patients with type 1 diabetes, those either about to attend a patient education course or those who had completed the course in the previous 10 years.SettingEstablished patient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 25 publications
(22 reference statements)
2
106
2
Order By: Relevance
“…Yet, patients' in-depth knowledge was sometimes seen as inappropriate, especially by non-specialized doctors who did not feel comfortable with patients showing a high level of expertise. These patients were therefore sometimes mistakenly considered as non-compliant by non-specialist doctors (Snow et al 2013). Also, providing more information was not always regarded as being a better approach.…”
Section: Information Provisionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, patients' in-depth knowledge was sometimes seen as inappropriate, especially by non-specialized doctors who did not feel comfortable with patients showing a high level of expertise. These patients were therefore sometimes mistakenly considered as non-compliant by non-specialist doctors (Snow et al 2013). Also, providing more information was not always regarded as being a better approach.…”
Section: Information Provisionmentioning
confidence: 99%
“…Regardless of the unequivocal positive aspects of good patient education, Snow et al (2013) pointed out a very important problem in modern medicine: not all physicians are happy about well-informed patients. Their in-depth knowledge is sometimes even understood as inappropriate and doctors and nurses may get uncomfortable with a high level of patients' expertise.…”
Section: Different Aspects Of Doctor-patient Relationship and Communimentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies described holistic approaches that could offer deeper understanding and provide models for future research. Snow and colleagues [34] coded whole stories by theme and created a summary document for each story to enable comparison across participants. Similarly, Stuckey and Tisdell [21] summarized interview transcripts in story form.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to concerns related to uncertainty, adjustment, and weariness, a longitudinal narrative interview study found that tension with healthcare professionals complicated diabetes self-care [34]. Participants were adults with type 1 diabetes completing a patient education course in the United Kingdom.…”
Section: Explaining Self-care and Treatment Challengesmentioning
confidence: 99%